A simple rule for prenatal diagnosis of total anomalous pulmonary venous return - Theera Tongsong (2018)
© 2016 by the American Institute of Ultrasound in Medicine. The objective of this series was to describe a simple rule for prenatal diagnosis of total anomalous pulmonary venous return (TAPVR). Fourteen fetuses had a prenatal diagnosis of TAPVR by the simple rule, including the following components: (1) the major criterion, which was the absence of a connection between the pulmonary vein and the left atrium; and (2) at least 1 of the following minor criteria: (a) the presence of a vascular confluence behind the atria, (b) abnormal spectral Doppler waveforms in the pulmonary veins, (c) a smooth posterior wall of the left atrium, (d) increased retroatrial space, (e) a dilated coronary sinus (cardiac type), (f) a dilated superior vena cava or brachiocephalic vein, and (g) an additional vessel on the 3-vessel/3-vessel and trachea view or a vertical descending vein. All were accurately diagnosed, and none were missed by the diagnosis. In summary, the simple rule described is helpful in increasing the number of accurate prenatal diagnoses of TAPVR.